Boosting Learner Motivation: Approaches to Increase Student Engagement in English Classes at SMA and SMK - Fachrurrozi Fachrurrozi; Bidarita Widiati (Global Education Journal, 2026)
In an increasingly globalized world, English has become a fundamental component of education, yet many students in non-native contexts exhibit low motivation and engagement in English language classes. This phenomenon is especially prevalent at the secondary education level, where students often perceive English as a mandatory subject with limited personal relevance. This study investigates practical strategies for enhancing learner motivation based on Self-Determination Theory (SDT), which emphasizes autonomy, competence, and relatedness. Using a qualitative descriptive design, data were collected from 6 English teachers and 40 students at SMA and SMK Darul Falah Mataram through semi-structured interviews, classroom observations, questionnaires, and document analysis. Thematic analysis revealed five key strategies that significantly improved student engagement: autonomy-supportive practices, real-world content integration, scaffolded feedback, collaborative learning activities, and technology-enhanced instruction. Findings show that students are more engaged when they are given meaningful choices, relevant materials, constructive feedback, supportive peer environments, and access to digital learning tools. These strategies address core psychological needs and foster intrinsic motivation, leading to more active participation and sustained interest in language learning. Notably, differences were observed between SMA and SMK students regarding the types of content and activities that most effectively motivated them, with SMK students showing stronger engagement when vocational English was integrated into lessons. The study recommends a shift from traditional teacher-centered methods to more student-centered, contextually responsive approaches to maximize learning outcomes and engagement in English language education at the secondary level.